Analysis of airborne GPS multipath effects using high-fidelity EM models - Geren, W.; Murphy, T.; Pankaskie, T. (IEEE transactions on aerospace and electronic systems, 2008)
Airborne GPS systems are being upgraded to provide sufficient positioning accuracy to support automatic landing operations in low visibility conditions. This is made possible by differential GPS (DGPS), in which the errors common to the airborne receiver and ground station are removed by knowledge of the latter's precise location. However, errors specific to the airborne system remain, of which the dominant components are receiver noise and multipath. To support the assessment of the integrity of the signal in space, these residual errors are incorporated in a statistically based error model, designated as the "standard model." The standard model is defined as the standard deviation of a Gaussian distribution that overbounds the residual pseudo-range (PR) error. It relates the standard deviation of the overbounding distribution to the elevation angle of the satellite relative to the local level coordinate system. The international community is currently developing improved standards to enable DGPS systems to support landings in the worst visibility conditions (i.e., CAT III). As a part of this development, the standard model for multipath is being re-evaluated and an improved model is sought. In order to better characterize the residual multipath errors, tools for accurate calculation of the airframe scattering effects are needed. Development of such tools is the subject of this paper. A new method for accurately computing pseudo-range error, based on the use of high-fidelity EM models, is described. This approach provides new insight into the mechanisms causing multipath error.